Análisis espacio temporal y determinación de la concentración de metales pesados en la laguna Yanamate, Cerro de Pasco, Perú - Menacho, Ernesto (2024)
The Yanamate lagoon was used for acid water discharge from 1981 to 2021, due to the mining activity of the Cerro S.AC mine, located in the province of Pasco, Pasco region. The objective of this research was to analyze the spatio-temporal variation of the water mirror of the Yanamate lagoon and to determine heavy metal concentrations. From Landsat 5 TM, Landsat 7 ETM+, Landsat 8 OLI, Landsat 9 OLI satellite images, the modified normalized difference water index (MNDWI) and the automated water extraction index without shading (AWEI_nsh) were calculated. These indices were used to analyze the spatiotemporal variation of the water mirror surface of the Yanamate lagoon, between the years 1985 and 2022, using the threshold segmentation method. Inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the concentration of heavy metals in the Yanamate lagoon, comparing the concentrations determined with the threshold values of the environmental quality standards (ECA). The spatio-temporal analysis determined an irreversible decrease in the surface area of the Yanamate lagoon's water mirror.  High concentrations of heavy metals were found in water and soil samples analyzed by ICP-MS, exceeding environmental quality standards (ECA). The soils and water analyzed are not suitable for agricultural use or for drinking by animals.